2018
DOI: 10.1080/10826068.2018.1466155
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemical characterization and evaluation of invertases produced from Saccharomyces cerevisiae CAT-1 and Rhodotorula mucilaginosa for the production of fructooligosaccharides

Abstract: Invertases are used for several purposes; one among these is the production of fructooligosaccharides. The aim of this study was to biochemically characterize invertase from industrial Saccharomyces cerevisiae CAT-1 and Rhodotorula mucilaginosa isolated from Cerrado soil. The optimum pH and temperature were 4.0 and 70 °C for Rhodotorula mucilaginosa invertase and 4.5 and 50 °C for Saccharomyces cerevisiae invertase. The pH and thermal stability from 3.0 to 10.5 and 75 °C for R. mucilaginosa invertase, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…According to such methodology, the optimal pH is 3.9 and temperature of 46.5ºC in Inv-I, and pH 3.9 and 45.6ºC in Inv-E. Such values are close to those found for invertases obtained from Saccharomyces cerevisiae, with optimum pH and temperature of 4.5 and 50ºC, respectively, as reported in the study conducted by Barbosa et al (2018). K. marxianus invertase obtained using by-products of food processing as a substrate…”
Section: Resultssupporting
confidence: 83%
“…According to such methodology, the optimal pH is 3.9 and temperature of 46.5ºC in Inv-I, and pH 3.9 and 45.6ºC in Inv-E. Such values are close to those found for invertases obtained from Saccharomyces cerevisiae, with optimum pH and temperature of 4.5 and 50ºC, respectively, as reported in the study conducted by Barbosa et al (2018). K. marxianus invertase obtained using by-products of food processing as a substrate…”
Section: Resultssupporting
confidence: 83%
“…The ability to produce FOS of β-fructofuranosidases from some species of the genus Rhodotorula has also been analyzed with different results. Curiously, enzymes from Rhodotorula sp.-LEB-V10 and Rhodotorula mucilaginosa only generated sugars included in the 1 F-FOS series, whereas that from Rhodotoula glutinis, a yeast synthesizing numerous valuable compounds (carotenoids and lipids among others) with a wide industrial usage, did not produce any type of FOS [22][23][24][25]. However, the large protein RdINV from Rhodotorula dairenensis (~170 kDa, of which N-linked carbohydrates constituted~16% of the total mass) produced mainly 6-kestose, but also a varied mixture of FOS of the three referenced series [26], which makes it of biotechnological interest.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Lincoln and More (2017) reported the inhibitory effects of Hg 2+ , Cu 2+ , pCMB, β-ME, and DTT on enzyme activity as well as the roles of Fe 2+ , Mg 2+ , and Mn 2+ as enzyme modulators on enzyme activity. Barbosa and co-workers (2018) found high structural stability of the enzyme produced by R. mucilaginosa . The data in the scientific papers clearly showed that the optimal conditions (pH and temperature) for invertase activity were 4.0 and 70 °C for R. mucilaginosa and 4.5 and 50 °C for S. cerevisiae .…”
Section: Discussionmentioning
confidence: 84%